Voluntariness and type of digital device usage: A study in terms of Vygotsky's cultural–historical perspective - Shatskaya, Arina; Gavrilova, Margarita; Chichinina, Elena (Frontiers in Psychology, 2023)
Digitalization of child development has been steadily increasing in recent years. Exploring the relationship between children's digital device exposure and their voluntariness still shows quite contradictory results. Screen time is the most studied factor on this issue. The purpose of the present study is to suggest the type of digital device usage as another factor in addition to screen time. In accordance with the cultural-historical perspective, digital device usage might be considered both as a psychological means and as entertainment. In accordance with the research hypothesis, the use of digital devices as a psychological means is related to higher voluntariness scores. The study sample was recruited from Moscow kindergartens and schools: preschoolers of 5–6 years old (n = 408) and 6–7 years old (n = 351), schoolchildren of 7–8 years old (n = 253) and 9–10 years old (n = 101). The study participants were involved in a voluntariness assessment performed via executive functions evaluation as well as in a semi-structured interview to identify their type and frequency of digital device usage. There are three findings of the present research. First, the "frequency of digital device usage" predictor proved i significant for the verbal working memory, inhibition, and cognitive flexibility at 7–8 years, as well as for verbal working memory at 6–7 years. Second, the number of children who use the digital devices as a psychological means increases as they grow older. Third, the children who use the digital devices as a psychological means tend to demonstrate higher mean scores for any executive function skills at 6–7 and 9–10 years old and for visual and verbal working memory at 7–8 years old. Multiple regression models did not confirm the significance of the "type of digital devices usage" predictor for executive function skills considering the participants' individual characteristics. This predictor is assumed more applicable to the children at the end of primary school and older, when exploring the executive functions in the context of children's digital device exposure.